2022
DOI: 10.15252/emmm.202115344
|View full text |Cite
|
Sign up to set email alerts
|

Intercepting IRE1 kinase‐FMRP signaling prevents atherosclerosis progression

Abstract: Fragile X Mental Retardation protein (FMRP), widely known for its role in hereditary intellectual disability, is an RNA-binding protein (RBP) that controls translation of select mRNAs. We discovered that endoplasmic reticulum (ER) stress induces phosphorylation of FMRP on a site that is known to enhance translation inhibition of FMRP-bound mRNAs. We show ER stress-induced activation of Inositol requiring enzyme-1 (IRE1), an ER-resident stress-sensing kinase/endoribonuclease, leads to FMRP phosphorylation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Liu and colleagues also showed that IRE1 interacts and promotes AMP-activated protein kinase phosphorylation exerting prosurvival signaling, nevertheless the direct/indirect modification remains unclear ( 119 ). The fragile X mental retardation protein (FMRP) was also identified as a new IRE1 kinase substrate, possibly regulating cholesterol transport and efferocytosis ( 150 ). In addition, pumilio, a RNA-binding protein in drosophila , was shown to be phosphorylated by IRE1, allowing its binding to XBP1 mRNA and protecting it against IRE1 RIDD activity ( 151 ).…”
Section: Ire1 Ppis Associated With Other Functions/outcomesmentioning
confidence: 99%
“…Liu and colleagues also showed that IRE1 interacts and promotes AMP-activated protein kinase phosphorylation exerting prosurvival signaling, nevertheless the direct/indirect modification remains unclear ( 119 ). The fragile X mental retardation protein (FMRP) was also identified as a new IRE1 kinase substrate, possibly regulating cholesterol transport and efferocytosis ( 150 ). In addition, pumilio, a RNA-binding protein in drosophila , was shown to be phosphorylated by IRE1, allowing its binding to XBP1 mRNA and protecting it against IRE1 RIDD activity ( 151 ).…”
Section: Ire1 Ppis Associated With Other Functions/outcomesmentioning
confidence: 99%
“…Drosophila FMR1 preferentially binds mRNAs containing m 6 A-marked ‘AGACU’ motif, which is mainly dependent on the hydrophobic network within FMR1 KH2 domain and contributes to maternal RNA degradation [ 60 ]. FMRP, positively regulated by IRE1, was also found to act as a translation repressor via polyribosome profiling and promote atherosclerosis by affecting macrophage cholesterol metabolism [ 61 ]. The discovery of novel m 6 A-recognizable RBPs will greatly facilitate our understanding of the role of RNA modifications in regulating immune cell function Figure 1C ).…”
Section: Other Readersmentioning
confidence: 99%
“…IRE1 inhibition leads to a remarkable reduction of plasma IL‐1β and IL‐18 levels in apolipoprotein E‐deficient mice (Tufanli et al, 2017). In addition, pharmacological suppression of IRE1 activity increases cholesterol efflux and apoptotic cell clearance, thereby reducing atherosclerosis in mice (Yildirim et al, 2022).…”
Section: The Three Upr Signaling Pathways Are Involved In Cardiovascu...mentioning
confidence: 99%